Assessing The Influence of Instagram Influencer Marketing on Follower Buying Intentions - Adzandri, Faraz; Ferdian, Feri (Lembaga Pengembangan Kinerja Dosen, 2024)
This study explores the relationship between influencer marketing and the buying intention among @tinandbel followers. This study was motivated by the Incompatibilities between the content published about @tinandbel's dining experience at the restaurant and the observed lack of a significant increase in customer numbers. This study's research methodology included quantitative techniques with a causal associative approach in addition to purposive sampling, which produced 120 samples. The data gathering approach uses a questionnaire with a Likert scale structure that has undergone validity and reliability assessments. With a percentage value of 65%, the R-squared results demonstrate that influencer marketing significantly affects purchase intention; the remaining 35% is accounted for by other factors. The hypothesis test results revealed a t-statistic of 12.13 > 1.96 and a p-value of 0.00 < 0.05, indicating that influencer marketing characteristics had a substantial impact on buying intention. These findings support the study's findings. According to the study's findings, Ha is accepted whereas H0 is denied.